Lessons in Corporate Governance from the Satyam Saga - Mehta, Jayashree (Prabandhan: Indian Journal of Management, 2009)
Post the Satyam saga, Corporate Governance is becoming an oft-repeated word. Satyam has been just about a year back, awarded the "Golden Peacock" for global excellence in corporate governance. Yet it collapsed within a year. This paper, after delving into the definition of corporate governance details out why did this happen. Large scale manipulation of figures, an highly "promoterized" board and hand-in-gloves auditors are some of the reasons for this sudden downfall. The three pillars-the investors, the regulators and the companies themselves need to inoculate themselves with these learnings towards a better tomorrow.